Dielectric properties of thermosetting material nanocomposites - Dias, Newton Luiz Filho; de Aquino, Hermes Adolfo; Pereira, Denise Souza; Rosa, Andre H. (Wiley-Blackwell, 2007)
The dieletric relaxation properties of thermosetting material nanocomposites based on spherosilicate nanoplatforms were studied from room temperature to 170 degrees C, varying the frequency from 10 to 1000 KHz. Permittivity (epsilon'), dielectric loss (epsilon ''), and activation energy (E-a) were calculated. The results of dielectric relaxation were confirmed by those of the final properties. The dielectric loss amplitude decreases with increasing ODPG content until about 70-73 wt % and slightly increases at higher ODPG content. This means that the increasing of the ODPG content in the composite samples decreases the number of pendants groups and/or increases crosslink densitv, causing decreased motion of organic tethers, and subsequently decreasing of the dipolar mobility. The results of apparent activation energy, fracture toughness and tensile modulus mechanical properties show the same profile with respect to ODPG content, in the sense that they exhibit maxima around 70 wt % ODPG. For the ODPG/MDA composites, this formulation of 70 wt % ODPG containing excess of amine is not composition where the highest crosslinked density is reached. This implies that the best mechanical properties and E-a are provided by some degree of chain flexibility. (c) 2007 Wiley Periodicals, Inc.
Keywords: dieletric relaxation; thermoset material; nanocomposite; spherosilicate